Gestión de la calidad en la prestaciones de los servicios hoteleros en el cantón Quevedo, año 2020 - Alvarez Lozano, Elsa Lisseth (2021)
Quality management has become an essential element for the tourism sector, and the hotel industry has taken this tool to meet the needs of customers, which is why this research work will detail the importance of implementing strategies in the quality of service offered. We can establish that quality management is defined as all the efforts made by a group of collaborators that allow the hotel in particular to establish standards according to the needs of customers who wish to enjoy each of the services offered in it. The services provided have to be effective to attract tourists by meeting the expectations of those who visit the hotels, so in this research an analysis of the techniques that should be applied in this research work will be conducted with the aim of implementing strategies to improve the quality of hotel services in the canton of Quevedo, in addition to specifying the proposed work to contribute to the analysis of the quality of services offered by hotels in Quevedo, determining the quality of services formulating some conclusions and recommendations to promote the hotel market in the canton.